Non-Linear Exchange Rate Pass-Through in Emerging Markets - Caselli, Francesca (IMF Working Papers; Working Paper ;, 2016)
This paper estimates exchange rate pass-through to consumer prices in emerging markets focusing on non-linearities and asymmetries. We document non-linearities and asymmetries in the transmission of exchange rate fluctuations to prices using local projection techniques to obtain state dependent impulse responses in a panel of 28 emerging markets. We find significant evidence of non-linearities during episodes of depreciation greater than 10 and 20 percent. More specifically, we find that, after one month, the exchange rate pass-through coefficient is equal to 18 and 25 percent respectively, compared to a coefficient of 6 percent in the linear case. We also investigate the role of temporary vs. permanent shocks and the adoption of an inflation targeting regime in the transmission from exchange rate movements to prices. We perform a set of robustness checks, addressing the presence of outliers and potential endogeneity concerns.